Neuroprotective potential of the pentacyclic oxindole alkaloids from Malaysian Uncaria longiflora var. pteropoda against hydrogen peroxide-induced sh-sy5y cells / Fatimah Salim, Mazatulikhma Mat Zain and Mohd. Syafiq Mohd. Ridzuan - Salim, Fatimah; Mat Zain, Mazatulikhma; Mohd. Ridzuan, Mohd. Syafiq (Research Innovation Business Unit, 2014)
The Uncaria (Rubiaceae) genus represents shrubby woody climbers distributed mainly in tropical regions, including Southeast Asia, Africa and South America, and Uncaria longiflora variety pteropoda is one of the fourtheen species found in Malaysia. Most of the species in the genus group are known for their medicinal properties. The more common representatives of Uncaria in Malaysia are Uncaria gambir along with Uncaria acida and Uncaria longiflora. From the uses described, Uncaria gambir may have anti-bacterial, anti-fungal and other properties that justify their uses in the treatment of burns and external callous ulcer and ‘sakit kudis’ which causes scurf or dry military scabs or crust formed on the skin. The fresh leaves and the young shoots of Uncaria gambir are used to cure diarrhoea and dysentery, and as a gargle for sore throats. For Uncaria acida and Uncaria longiflora variety pteropoda, the leaves are rubbed on the body to relieve pain from rheumatism, while their juice is used for trush and mixed with iron-rust for framboesia. Biological and pharmacological activities of Uncaria species have generally focused on the plant fractions or specific constituents which are used in herbal Uncaria preparations. However, studies on the isolated pure compounds and/or a combination of them have been reported. The majority of the activities observed were attributed to the alkaloid constituents of the plant, while some of the effects were contributed by the terpenoids and flavonoids constituents. Among the crude extracts of Uncaria, Uncaria tomentosa or known as cat’s claw has been the most widely studied, followed by Uncaria rhynchophylla and among the compounds isolated from the genus, the alkaloid rhynchophylline has been the most pharmacologically explored. Although, many reports were found on the pharmacological activities of Uncaria, not much has been reported on the local Uncaria plants. Interestingly, our work on the biological screening on five Malaysian Uncaria species has found Uncaria longiflora variety pteropoda to possess strong antioxidant properties, which reported to correlate well with the neuroprotective activity. Thus, the current study has evaluated for the first time the neuroprotective, cytotoxic and neurotoxic roles of five known pentacyclic oxindole alkaloids (POAs) reported in the stems of Uncaria longiflora variety pteropoda [rauniticine-allo-oxindole B (1), isopteropodine (3), pteropodine (4), uncarine F (6) and isopteropodic acid (7)] on the human neuroblastoma SH-SY5Y cell line. Cell survival was measured using the MTS assay [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl) 2-(4-sulfophenyl)-2H-tetrazolium bromide)], and analysed colorimetrically at a wavelength of four hundred ninty five nano meter (495 nm). Alkaloid 6 was found to possess a dual property by reducing the cell survival of both cancer and normal cells at one thousand micro molar (1000uM) while alkaloid 4 was found to reduce cell survival of the normal cells at the same concentration. Investigation on the protective potential in response to the deleterious hydrogen peroxide induced (H2O2-induced) changes on mitochondrial function nevertheless found that they protected the normal cells in the lowest evaluated concentrations [zero point zero one to one micro molar (0.001 - 1 uM)] and thus increase on the neuronal cell survival up to twenty two percent (22%) and thirty percent (30%), respectively, above the positive control. In addition, in the same assay, three other alkaloids (1, 3 and 7) showed significant protective properties by increasing the neuronal cell survival up to eighty-three to ninety six percent (83-96%) compared to fifty two percent (52%) for the positive control suggesting their potential as anti-neurodegenerative agents. Since consistent evidence has demonstrated the contribution of hydrogen peroxide (H2O2) on both progression and pathological development of several human diseases associated with oxidative stress, alkaloids 1, 3 and 7 are worthy of further investigation on neuroprotective properties